Abundance of invasive grasses is dependent on fire regime and climatic conditions in tropical savannas. (1st October 2020) - Damasceno, Gabriella; Fidelis, Alessandra
Abstract: Invasive grasses are a threat to some tropical savannas, but despite being fire-prone ecosystems, little is known about the relationships between fire season, climatic conditions and invasive species on these systems. We evaluated the response of the perennial invasive grasses Melinis minutiflora and Urochloa brizantha to three fire seasons in an open tropical savanna in South America: Early-Dry (May), Mid-Dry (July) and Late-Dry (October) in relation to unburned Controls. Moreover, we investigated how these responses were influenced by precipitation and extreme air temperatures. We hypothesized that biomass of both species would be reduced by fires during their reproductive period and that climatic conditions would affect them equally. We conducted prescribed burns on 15 × 15 m plots (4 plots x 4 treatment x 2 invasive species = 32 plots) in 2014. We sampled the biomass before the burn experiments and for the next two years (five 0.25 m 2 samples/plot). Our experiments revealed that the fire season did not influence the abundance of either species. However, the two species responded differently to fire occurrence: M. minutiflora decreased whereas U. brizantha was not affected by fires. Early-Dry and Late-Dry fire treatments enhanced the replacement of M. minutiflora by U. brizantha . We found that the influence of precipitation depended on the species: it reduced M. minutiflora but increased U. brizantha abundance. Lower monthly minimum temperatures decreased the abundance of both species. It directly reduced live M. minutiflora and increased dead U. brizantha biomass. Monthly maximum temperatures affected the invasive grasses by reducing live M. minutiflora . Since tropical savannas are predicted to face climatic instability and that climate influences the differential response of invasive species, the management of invaders should consider both the identity of the target species and the possible interactions with other invasive species. Moreover, it is essential to keep an adaptive management approach to face the uncertainties that climate change may pose to biodiversity conservation. Highlights: Disturbance regime must focus into the target invasive grass species. Managers should be aware of the turnover in dominant invasive species. Climate distinctly affect management's results due to its influence on invasive species. Climate change should be considered in future management plans for control of invasive species.